Unformed and unfilled a critique of the Gap Theory - Fields, Weston William (Phillipsberg, NJ Presbyterian and Reformed, 1976)
Includes bibliographical references and indexes.
Keywords: Bible. O.T. Genesis I 2 -- criticism, interpretation, etc; Gap theory -- evidences